Evaluation of bael (Aegle marmelos Correa.) varieties for growth, yield and quality under semi-arid conditions of Madhya Pradesh (Indian Journal of Arid Horticulture, 2025)
This study aimed to evaluate the performance of various bael varieties under the Kymore Plateau and Satpura Hills agro-climatic zone of Madhya Pradesh over a three-year period (2021-22, 2022-23 and 2023-24). A total of seven bael varieties (Goma Yashi, Narendra Bael-5, Narendra Bael-7, Narendra Bael-9, Narendra Bael- 17, CISH Bael-1 and CISH Bael-2) were assessed for growth, yield, and quality parameters. The results indicated that CISH Bael-2 recorded the highest number of fruits per plant (33.96), while Narendra Bael-7 exhibited the heaviest fruit weight (3.97 kg) and the highest pulp percentage (70.71%). CISH Bael-1 demonstrated the greatest plant height (6.52 m), stem girth (76.30 cm), and TSS (39.69°Brix), highlighting its potential for high-quality fruit production. The findings suggest that CISH Bael-2 and Narendra Bael-17 are ideal for high-yield cultivation, while CISH Bael-1 is best suited for superior fruit quality. This study provides valuable insights for the selection of suitable bael varieties for commercial production in semi-arid regions of Madhya Pradesh.